Why is the share of women willing to work in East Germany larger than in West Germany? A logit model of extensive labour supply decision - Beate Grundig (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2008)
The aim of the paper is to analyse differences in the labour force participation (LFP) between East and West German women. Using microcensus data in a binary choice model, we distinguish three main explanations for these differences: the skill composition, the regional labour market and childcare availability. As LFP in-creases in the skill-level, the larger share of high-skilled women in East Germany can explain more than 10 percent of the differences. Whereas East German women do not vary their efforts when regional labour market conditions worsen, West German women are discouraged thereof. Female LFP in East Germany is positively influenced by the provision of full-time childcare while West German women do not show any significant reaction.
Keywords: J13; J22; R23; 330; Female labour supply; childcare; logit model; decomposition